Strategize product strategy and product roadmap practices for the digital age - Pichler, Roman (Pichler Consulting, 2022)
Using a wide range of proven techniques and tools, product management expert Roman Pichler explains how to create a winning product strategy and actionable roadmap. Comprehensive and insightful, the book will enable you to make the right strategic decisions in today$1 (Bs dynamic digital age. If you work as a product manager, Scrum product owner, product portfolio manager, head of product, or product coach, then this book is for you.s
Keywords: Strategy